ON THE HISTORY AND MODERN CONDITION OF THE ERASMIAN PRONUNCIATION OF ANCIENT GREEK - Лазер-Паньків, Олеся; Залевський, Іоан (Taras Shevchenko National University of Kyiv (Ukraine), 2021)
The article presents the results of a study of some aspects of the formation and use of Erasmian pronunciation of the Ancient Greek language (in particular, the vagueness of the concept, lack of standardization and certain linguistic inconsistencies), based on analysis of the original work of Erasmus of Rotterdam "Dē rēctā latīnī graecīque sermōnis prōnūntiātiōne dialogus" and works devoted to the analysis of Ancient Greek pronunciation and the history of the Greek language in general. Attention is paid to the non grata status that Erasmian pronunciation has in Greece, as well as to alternative views on the origins of the mentioned work of Erasmus, to which, from the 16th century to the present day, opponents of both the Erasmian pronunciation and the reconstructed systems in general refer. Some important facts from the history of Erasmian pronunciation are outlined, in particular that Erasmus was not the pioneer in the search for the "true" pronunciation of Classical Greek (a Spanish humanist Antonio de Nebrija researched this issue at least a quarter of a century before the publication of Erasmus's work); in writing the Dialogue, Erasmus relied on the work of his predecessors, with whom he was maintaining friendly communication; Erasmus's work was not a clear enough proposal for a new reformed system, and the scholar himself continued to use the Byzantine pronunciation and recognized its status. The article gives examples of some differences between variants of Erasmian pronunciation. It is concluded that the Erasmian pronunciation from its inception was not a clearly defined system, and, despite the revolutionary and impressive breakthrough of this linguistic initiative, had some errors, which were compensated by later attempts in the Ancient Greek pronunciation reconstruction in the 19th–21st centuries. It is suggested that, given the significant non-uniformity of present-day Erasmian pronunciation variants (which sometimes leads to complications in international communication between specialists), it is advisable to use, or at least be familiar with modern, more clearly defined and scientifically sound reconstructions, and / or Modern Greek pronunciation which is especially important for rapport with Greek colleagues in classical studies. * One of the authors of the article is the member of the editorial board of the "Bulletin of Taras Shevchenko National University of Kyiv. Literary studies. Linguistics. Folklore Studies", and therefore they do not participate in the review and decision-making process regarding the publication of this article.

Представлено результати дослідження деяких аспектів формування та використання Еразмової вимови давньогрецької мови (зокрема, розмитість самого поняття, відсутність стандартизованості й певні лінгвістичні невідповідності), здійсненого на основі аналізу оригінального твору Еразма Ротердамського "Dē rēctā latīnī graecīque sermōnis prōnūntiātiōne dialogus", а також теоретичних напрацювань, присвячених аналізу давньогрецької вимови та історії грецької мови загалом. Приділяється увага статусу non grata, який Еразмова вимова має у Греції, а також альтернативним версіям щодо задуму й обставин створення згаданого твору Еразма, до яких, від XVI ст. і дотепер, апелюють опоненти як Еразмової вимови, так і реконструйованих систем загалом. Окреслюються деякі важливі факти з історії виникнення Еразмової вимови, зокрема, що Еразм не був першовідкривачем у пошуках "істинної" вимови класичної грецької мови (щонайменше за чверть століття до видання праці Еразма це питання досліджував іспанський гуманіст Антоніо де Небріха); у написанні "Діалогу" Еразм спирався на напрацювання попередників, із якими підтримував дружнє спілкування; твір Еразма не був достатньо чіткою пропозицією нової реформованої системи, а сам учений продовжував користуватися візантійською вимовою та визнавав її чинний статус. Наведено приклади деяких розбіжностей між варіантами Еразмової вимови. Зроблено висновок, що Еразмова вимова від самого її зародження не була чітко визначеною системою, і, незважаючи на революційність і вражаючий прорив цієї мовознавчої ініціативи, мала певні помилки, які були компенсовані пізнішими спробами реконструкції давньогрецької вимови у XIX–XXI ст. Доведено, що, зважаючи на суттєву неуніфікованість сучасних варіантів Еразмової вимови (що подекуди призводить до ускладнень практичного характеру в міжнародній комунікації спеціалістів), доцільним є використання, або, принаймні, прикладне знайомство з сучасними, більш чітко визначеними й науково обґрунтованими реконструкціями, та / або новогрецькою вимовою, яка особливо важлива задля взаєморозуміння з грецькими колегами-класиками. * Один з авторів статті є членом редакційної колегії «Вісника Київського національного університету імені Тараса Шевченка. Літературознавство. Мовознавство. Фольклористика», тому не брав участі у рецензуванні та прийнятті рішення щодо публікації цієї статті.
ПРО ІСТОРІЮ ТА СУЧАСНИЙ СТАН ЕРАЗМОВОЇ ВИМОВИ ДАВНЬОГРЕЦЬКОЇ МОВИ
Keywords: Erasmian pronunciation; Ancient Greek; Erasmus of Rotterdam; reconstruction of Ancient Greek pronunciation; Еразмова вимова; давньогрецька мова; Еразм Ротердамський; реконструкція давньогрецької вимови